Penegakan Hukum Terhadap Pelaku Tindak Pidana Perjudian Online - Zainudin Hasan; Incik Daffa Apriano; Yunika Sari Simatupang; Amanda Muntari (Jurnal Multidisiplin Dehasen (MUDE), 2023)
The current development of information technology has brought people into the era of globalization which gives freedom to everyone in the world to socialize with anyone and wherever they are. The development of misused information technology has led to more modern crimes, namely online gambling using the internet as a means of committing crimes. Gambling is still one of the crimes in Indonesia and is increasingly widespread in cyberspace through online media. The community really supports law enforcement against this online gambling crime. With that in mind, this study aims to find a way out for law enforcement in combating online gambling crimes from the perspective of criminal law and legal responsibility for perpetrators of online gambling crimes based on the perspective of criminal law.